Assessment of Knowledge among Dental Patients regarding Second wave of Corona virus Disease - Kanwal Zulfiqar, Syed Hamza Zia, Ghina Rizwan, Zarnab Rizwan, Naeema Iqbal, Mobina Fatima Zulfiqar, (Journal of Rawalpindi Medical College, 2022)
Objective The objective of this study was to assess the dental patients' knowledge and perspectives with respect to the second wave of COVID-19. Materials and methods A self-designed questionnaire was sent as a google forms link via WhatsApp and a few patients who had no access to WhatsApp, were asked to fill out a hand printed form. The completed questionnaires were then analyzed using the statistical package for social sciences (IBM version 22). Results: A total of 350 participants were included in the study, out of which 38% were male and 62% were female. Result was calculated using binary logistic regression analysis for different variables to predict the confidence level based on their knowledge, attitude and practice regarding second wave of COVID-19. Conclusion: Our study concluded that there is more than satisfactory level of knowledge regarding COVID-19 and People are aware of the basic protocols which help in protection against the virus owing to easy access of information.